The influence of a KCl-rich environment on the corrosion attack of 304 L: 3D FIB/SEM and TEM investigations. (1st May 2021) - Phother-Simon, J.; Hanif, I.; Liske, J.; Jonsson, T.
Highlights: KCl(g) deposition at 600 °C introduced alloy grain boundary corrosion on the austenitic stainless steel 304 L. The complex alloy GB attack was investigated in detail by 3D volume reconstruction (FIB/SEM) combined with TEM/EDX. Initiation/growth of the accelerated alloy GB attack is suggested to be caused by fast diffusion of Fe/Cr at the GB regions. Small amounts of chlorine were detected within the large depletion zones with and without oxygen. Abstract: This study investigates the intergranular corrosion of a stainless steel (304 L) in the presence of KCl(g)/KCl(s) at 600 °C by using a FIB/SEM to perform 3D reconstruction/tomography of grain boundary attacks in combination with TEM. The investigation shows that the combination of the 3D FIB/TEM offers a great potential for the study of complex features, i.e. intergranular corrosion. The initiation and propagation of the grain boundary attack occurred very rapidly below an intact secondary protection. No large accumulations of metal chlorides were observed at the grain boundary regions. Instead, indications of very rapid alloy diffusion in grain boundary regions were observed.